PRACTICE OF PUNISHMENT FOR CORRUPTION CRIMES - M. P. Kleymenov; I. M. Kleymenov; R. V. Pustovit (Правоприменение)
The subject. The central element in combating corruption is punitive practice. The whole history of mankind testifies that corruption can be restrained only by effective application of criminal punishment.The purpose of the article is to show the practice of assigning criminal punishment for cor-ruption crimes of various kinds.The description of methodology. The authors use the conception criminally-legal response. The following characteristics of the criminal-legal response are distinguished: lack of response; very weak response – the number of convicts does not exceed 10; weak response – the num-ber of convicts is calculated within a few dozen people; adequate response – the number of convicts and penalties correspond to the criminological characteristics of a group of crimes; intensive reaction – the norm is realized in conditions of the possibility of ensuring the inevi-tability of punishment; punitive response – the norm is applied on the basis of the "letter, not the spirit" of the law; reflexive response – the appointment of punishment to privileged crim-inals in conditions of increased public attention; protest reaction – judicial practice comes into conflict with ill-conceived legislative novels.The main results and scope of their application. The practice of imposing punishment for corruption crimes in the following spheres is ana-lyzed: electoral; public service; commercial-service relations; of justice.Conclusions. Punitive practice in relation to persons convicted of corruption crimes in gen-eral is characterized by exceptional humanism. As the main penalties the penalty is leading (50.1%), in the second place – suspended imprisonment (24.1%). Real deprivation of liberty applies only to the seventh part of corrupt officials (14.7%). For comparison: according to art. 158 "Theft" in 2016 was sentenced to imprisonment twice as many criminals – 30,3%. This ratio indicates an underestimation of the public danger of corruption crime and actu-ally disavows the proclaimed thesis that corruption is a systemic threat to national security.